Communication in interfaith and multiethnic-racial families: Navigating identity and difference in family relationships. (June 2023) - Warner Colaner, Colleen; Atkin, Annabelle L.; Elkhalid, Amnee; Minniear, Mackensie; Soliz, Jordan
The current manuscript provides a critical review of family communication in multiethnic-racial and interfaith families. The review specifically focuses on differences related to religious and ethnic-racial identity, given that both are salient aspects of self-concept tied to psychosocial well-being, exist in a sociocultural environment characterized by racialized structures and systems of privilege, have been problematized through a deficit approach, and have implications for how to constructively address religious and ethnic-racial differences outside of the family. We begin by defining the three core concepts: (a) interfaith, (b) multiethnic-racial, and (c) family. We then discuss our methodology for selecting and reviewing empirical research and provide a synthesis of findings for each family type. We specifically address how interfaith then multiethnic-racial families communicate to address socialization and identity development, integrate differences, and combat bias. We conclude with a critical summary, arguing that interfaith and multiethnic-racial families are more accurately characterized through their strengths rather than difficulties. We point to limitations of current work, namely that research is largely based on Western perspectives on race/ethnicity and Ibrahimic religious traditions, that children and adolescent perspectives are relatively absent, and that the research tends to primarily focus on communication between couples or in parent-child relationships rather than extended family networks. Trajectories for future research include a focus on the manner in which communication surrounding identity and difference impacts self-concept and psychosocial well-being as well as contextualizing experiences of multiethnic-racial and interfaith families within the sociocultural environment. Our articulated conceptual landscape and synthesis of the research shed light on these complex relationships and encourage ongoing scholarship on these relatively understudied family forms.